Reducing Family Violence Through Child Welfare Intervention: A Propensity Score-Matched Study of Fathers for Change - Beebe, Rebecca (Journal of interpersonal violence, 2023)
Intimate partner violence (IPV) is prevalent, costly, and detrimental to children’s health and development. It often co-occurs with child abuse and neglect. Most children referred to child protective services (CPS) have witnessed IPV and are at increased risk for subsequent exposure, as well as repeat maltreatment. For CPS referred children, there is often a missed opportunity to interrupt family violence and prevent future occurrences. Fathers for Change (F4C) is a family level intervention designed to reduce IPV by improving emotion regulation and reflective functioning in fathers. To date, no study has examined whether F4C is associated with reduced recidivism in families referred to CPS. Using propensity score matching (PSM) to simulate an experimental design, the current study tests the hypothesis that families with fathers who completed F4C will have significantly lower rates of new CPS reports over a 12-month period compared to a PSM sample of families of fathers not referred to F4C. Data were extracted from a state CPS electronic case records system on all accepted child maltreatment reports received between January 1, 2015, and April 30, 2020. PSM was successful in balancing potential confounders (e.g., race, number of prior maltreatment reports, risk level, date of report), resulting in a comparison group approximate to one that could be achieved via a randomized control trial. Logistic regression analyses of 1:1 PSM pairs revealed that control fathers were 2.4 times more likely to have a repeat maltreatment report during the 12-month follow-up period than F4C fathers. These findings suggest that F4C may provide an effective approach for reducing risk of repeat maltreatment among CPS referred children with identified IPV exposure.